(untitled) (Bangladesh Journal of Nutrition, 2012)
Proximate composition and mineral content of five species of edible mushrooms namely Pleurotus ostreatus, Pleurotus sajor-caju, Pleurotus florida and Pleurotus HK- 51 belonging to the family: Pleurotaceae and genus: Pleurotus and Calocybe indica belonging to the family: Tricholomataceae and Genus: Calocybe have been analyzed.Crude protein, total lipids, available carbohydrates, dietary fiber and total carbohydrates content in mushrooms were found to be in the ranges of 3.22-4.83, 0.41-1.05, 4.2-6.37, 0.58-1.11 and 4.82-7.48 g per 100g of fresh edible portion(EP) respectively. Moisture, total solids and ash content were found to be in the ranges of 85.95-90.07, 9.93-14.05 and 0.98-2.3 g/100g of fresh EP respectively. Where as total calorie values in mushrooms were found to be in the ranges of 35.51 - 50.03 Kcal / 100g fresh EP. The values of Zinc, copper, iron, sodium and potassium content in mushrooms were found to be in the ranges of 0.65-1.24, 0.14-0.91, 0.94- 1.81, 3.18-37.23 and 19.83-197.24 mg/100g of fresh EP respectively while calcium, magnesium, phosphorus and manganese content were in the ranges of 0.12-0.58, 27.26-51.21, 22.2-62.1 and 0.17-0.53 mg/100g of fresh EP respectively. DOI: http://dx.doi.org/10.3329/bjnut.v22i0.12832 Bangladesh Journal of Nutrition Vol.22-23 2009-2010 pp.61-68